Using some of unusual waste vegetable oils as fat supplements in growing rabbit rations - Abd El Rahim M.I.; Tawfeek M.I.; Ahmed S.S.; Amin R.S. (Rabbit production in hot climates, 1994)
The objective of this study was to evaluate two types of acidulated soapstock of either palm oil (APS) or mixture oils (AMS) in comparison with corn oil as cheap supplement fats when added at 1 per cent to the commercial rabbit ration. Fatty acids profile of different fat types were determined by using GLC. The effect of additional fats was determined on growth response, nutrient utilization, blood serum metabolites and slaughter performance. Four groups of 60 weanling NZW rabbits (average body weight, 537 +/- 32 g) were given for 8 weeks a commercial diet without (control) or supplemented with 1 per cent of any of: corn oil (group 2), acidulated palm oil soapstock (group 3) and acidulated mixture oils soapstock (group 4). The percentage of C18:2 (linoleic) in corn oil was higher than in AMS and APS. However, the percentages of C18:3 (linolenic) and C20:4 (arachidonic) were the highest in AMS and APS. The daily weight gain, feed conversion efficiency and viability of rabbits showed insignificant improvement with the acidulated sopastock diets. The digestibility of CF, percentage of N-retained, activity of GOT enzyme and dressing percentages were increased (P less than 0.01 or 0.05) by addition of the acidulated soapstock of either APS or AMS. Serum cholesterol level in rabbits was elevated (P less than 0.05) with APS diet, while it decreased by AMS supplementation.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)